2019
DOI: 10.17860/mersinefd.596817
|View full text |Cite
|
Sign up to set email alerts
|

Karar Verme Süreci

Abstract: Öz: Örgüt yönetiminde, karar verme yönetim süreçlerinin en başında yer gelir. Karar verme, örgütün amaçları doğrultusunda yollar, imkânlar ve araçlar arasından bir seçim yapmayı içeren zihinsel, bedensel ve duygusal süreçlerin toplamıdır. Örgüt dışı faktörlerden kısa zamanda fazlaca etkilenen eğitim örgütleri için, birden fazla nitelik ve nicelik içeren kriter ve amaç söz konusu olduğunda Çok Kriterli Karar Verme (ÇKKV) yöntemleri öne çıkmaktadır. Çok kriterli karar verme yöntemleri, ölçülebilen ve ölçülemeyen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The study revealed that principals scored the highest in rational style. This finding is consistent with previous research findings about the decision-making styles of school principals (Acar, 2020;Çetinyol, 2019;Ölçüm, 2015;Özgenel, 2017;Yıldız, 2012). Those with a rational style are prudent individuals who double-check their sources of information for accuracy and make logical and systematic decisions based on knowledge (Scott & Bruce, 1995).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study revealed that principals scored the highest in rational style. This finding is consistent with previous research findings about the decision-making styles of school principals (Acar, 2020;Çetinyol, 2019;Ölçüm, 2015;Özgenel, 2017;Yıldız, 2012). Those with a rational style are prudent individuals who double-check their sources of information for accuracy and make logical and systematic decisions based on knowledge (Scott & Bruce, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…This study is expected to add to the literature by describing social entrepreneurship characteristics and decision-making styles, which are thought to be directly related to leadership, and analyzing the relationship between these variables. When studies on the decision-making styles of Turkish school administrators are examined, it is discovered that the administrators prefer a rational decision-making style (Acar, 2020;Kurban & Yaşar, 2015;Oğuz, 2009;Ölçüm, 2015;Özgenel, 2017;Yıldız, 2012). School administrators' decision-making styles are a significant predictor of problem-solving skills and creative thinking disposition (Özgenel, 2017), communication skills (Tekin, 2019), transformational leadership characteristics (Oğuz, 2009), psychological resilience (Yıldız, 2015), procrastination tendencies (Acar, 2020;Uğurlu, 2013) and well-being (Uslu, 2016).…”
Section: Introductionmentioning
confidence: 99%